The Interpretation of Freedom in the Letters of Paul - Coppins, Wayne (Mohr Siebeck, 2009)
Wayne Coppins investigates the interpretation of freedom in Paul's letters with special reference to Martin Luther and twentieth-century "German" New Testament scholarship. He focuses on three key issues, namely the importance of freedom in Paul's letters and theology, the centrality and meaning of "freedom from the law," and the relationship between freedom and service. In addition to providing a detailed exegesis of the key Pauline texts, the monograph also offers a synthesis of the aforementioned issues and concludes with a retrospective assessment of the promise and pitfalls of 'German' scholarship on freedom in Paul. While critical of the assumption that Paul himself had already developed a unified concept of freedom, the author suggests that it may nevertheless be appropriate to employ freedom as a category for depicting Paul's thought.